Influence of replacement of Mn by Cr on magnetocaloric properties of quenched NiMn1–xCrxGe alloys - Zubov, E.; Szytuła, A.; Dyakonov, V.; Ślawska-Waniewska, A.; Bażela, W.; Valkov, V.; Marzec, M.; Tyvanchuk, Yu.; Dyakonov, K.; Sivachenko, A.; Nedelko, N.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
In this paper, the crystallographic, magnetic, thermomagnetic, and magnetocaloric properties of the quenched NiMn1–xCrxGe (x = 0.04, 0.18 and 0.25) half-Heusler alloys have been studied by x-ray diffraction, differential scanning calorimetry and magnetization measurements. An influence of partial substitution of Cr for Mn and quenching of the samples on the character of structural and magnetic phase transitions is presented. Quenching of the alloys results in the formation of two phase (orthorhombic and hexagonal) crystal structure. The magnetic properties were investigated by means of magnetization measurements over a wide temperature (5–400 K) and magnetic field (up to 60 kOe) ranges. The experimental data indicate that at quenching and with increasing Cr content the magnetic order changes from antiferromagnetic to ferromagnetic. Hardened compounds exhibit a thermal hysteresis in the vicinity of the magnetic phase transition, what is characteristic for a first-order magnetic phase transition. The magnetic phase transition temperatures are decreased as a result of quenching of the samples. The magnetic entropy changes were calculated using the field dependences of isothermal magnetization in terms of the thermodynamic Maxwell relation. The magnetic entropy changes, |ΔSMmax|, obtained for the hardened alloys with x = 0.25 have the maximum value equal to 23 J/(kg·K) near the magnetic phase transition for a field change of ΔH = 0–60 kOe.